Radiological Monitoring of the Treatment of Solid Tumors in Practice - Ganten, M. K.; Ganten, T. M.; Schlemmer, H. P. (RöFo - Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2014)
Purpose: Thanks to advances in cancer therapy, the diagnosis of “incurable cancer” is increasingly able to be changed to a chronic disease that is manageable over long periods, resulting in a change in the clinical management of cancer patients with solid tumors. New parameters are needed to measure the success of targeted therapy in clinical trials.Materials and Methods: Review article on the basis of selective literature research.Results: In order to assess how well solid tumors respond to treatment, size-based criteria called RECIST (Response Evaluation Criteria in Solid tumors) have been defined. These criteria have been validated in large oncology trials and are currently used most frequently. New molecular therapies often do not – or at least do not immediately – reduce the size of a tumor. Therefore, RECIST evaluation should be critically assessed especially in the case of modern therapies. Any additional available tumor biology information should be considered. In radiology new methods and developments of RECIST have been introduced to better assess the success of targeted therapy.Conclusion: Assessment according to RECIST has been proven for the follow-up of classic tumor therapy. For the monitoring of targeted therapies, new parameters are often required. Therefore, some specific tumor- and therapy-adapted criteria have already been defined to better evaluate treatment success in clinical trials.Key points:• Follow-up evaluation of treatment is becoming increasingly important in modern oncology.• Conventional cytostatic/cytotoxic treatments can be evaluated on the basis of size according to RECIST.• However, approx. 80 % of newly approved oncological agents are based on molecular mechanisms of action.• In the case of molecular treatment forms, the tumor volume does not necessarily correlate with the course of the disease.• Therefore, there are new practice-relevant treatment-adapted and tumor-adapted imaging methods.Citation Format:• Ganten MK, Ganten TM, Schlemmer HP. Radiological Monitoring of the Treatment of Solid Tumors in Practice. Fortschr Röntgenstr 2014; 186: 466 – 473
Keywords: CT; metastases; staging